2020
DOI: 10.1101/2020.03.31.20048900
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Correction of Artifacts Induced by B0 Inhomogeneities in Breast MRI using Reduced Field-of-View Echo-Planar Imaging and Enhanced Reverse Polarity Gradient Method

Abstract: Purpose: Diffusion weighted (DW) echo-planar imaging (EPI) is prone to geometric and intensity distortions due to B0 inhomogeneities. Pulse sequences that excite spins within a reduced field-of-view (FOV) in the phase encoding (PE) direction have been developed to decrease such distortions. In addition, use of the reverse polarity gradient (RPG) method, a retrospective approach to correct distortion artifacts, has been shown to improve the localization of tumor lesions. The purpose of this work was to evaluat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…A salient question, however, is whether this correction actually produces images that more accurately reflect anatomy. The consistent increases in MI between DWI b=0 and T2 images after DisCo is in line with prior work that performed MI-based analyses in other organs (17, 20). We further showed that applying RPG can lead to reduction in error between anatomic landmarks annotated on diffusion and structural images (Figure 5).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A salient question, however, is whether this correction actually produces images that more accurately reflect anatomy. The consistent increases in MI between DWI b=0 and T2 images after DisCo is in line with prior work that performed MI-based analyses in other organs (17, 20). We further showed that applying RPG can lead to reduction in error between anatomic landmarks annotated on diffusion and structural images (Figure 5).…”
Section: Discussionsupporting
confidence: 89%
“…Prior studies have demonstrated that B0 inhomogeneities affect organ or lesion localization in the prostate and breast (16, 17, 20). The extent of B0 inhomogeneities and their consequent artifacts depend, in part, on the anatomic environment of a lesion (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced field of view (rFOV) improves spatial resolution and decreases artifacts by limiting the field of view and number of k-space lines in the phase-encoding direction ( 99 , 100 ). Improved image quality with rFOV compared to standard DWI techniques has been shown to enhance lesion conspicuity and morphologic assessment in the breast ( 101 104 ).…”
Section: Validation and Technical Considerationsmentioning
confidence: 99%
“…T 2 -weighted, conventional DWI (b=0 s/mm 2 ), full FOV EPI (b=0 s/mm 2 ), and reduced FOV EPI (50% phase field of view) (b=0 s/mm 2 acquired at 3T) images are shown. Reduction of percent phase encoding direction to 50% reduces geometric distortions caused by B 0 -inhomogeneity, especially in the nipple region ( 100 ).…”
Section: Validation and Technical Considerationsmentioning
confidence: 99%
“…In addition to T 1 -and T 2 -weighted images, axial reduced field-of-view (FOV) echo-planar imaging DW-MRI was performed with the following parameters: spectral attenuated inversion recovery (SPAIR) fat suppression, echo time (TE) = 82 ms, repetition time (TR) = 9000 ms, b-values (number of diffusion directions) = 0, 500 (6), 1500 (6), and 4000 (15) s/mm 2 , gradient pulse duration (δ) = 29.34 ms, gradient pulse time interval (∆) = 37.67 ms, FOV = 160 × 320 mm 2 , acquisition matrix = 48 × 96, reconstruction matrix = 128 × 128, voxel size = 2.5 × 2.5 × 5.0 mm 3 , phase-encoding (PE) direction anterior-posterior (A/P), and no parallel imaging. The b = 0 s/mm 2 volumes were collected in the A/P and posterior-anterior (P/A) PE directions to correct DW-MRI data for geometric and intensity distortions due to B 0 inhomogeneities using the reverse polarity gradient (RPG) method [26,27]. For the diffusion sequence, δ and ∆ time constants were fixed, while the gradient magnitude was manipulated to produce different b-values.…”
Section: Mri Data Acquisitionmentioning
confidence: 99%